TUHAN, MANUSIA, ALAM DAN PENGETAHUAN DALAM FILSAFAT PENDIDIKAN BARAT DAN ISLAM : SEBUAH ANALISIS KOMPARATIF - Muhammad Zainudin Zain; Nasrullah Nasrullah (Makkah: Journal Of Islamic Studies, 2025)
This study analyzes the relevance of Islamic epistemology, which integrates revelation, reason, and sensory experience, in explaining the concepts of God, humanity, nature, and knowledge within the context of contemporary philosophy of education. The research is motivated by phenomena such as moral crisis, environmental degradation, spiritual disorientation, and human fragmentation that arise from the dominance of Western rationalist and empiricist paradigms, which tend to separate transcendental values from educational processes. Through a comparative analysis of rationalism, empiricism, and Islamic epistemological theory, this study demonstrates that the Islamic approach offers a more holistic and integrative epistemological framework. Islamic epistemology not only positions reason and experience as valid sources of knowledge but also places revelation as an ethical and spiritual foundation that directs the goals of education. The findings reveal that the integration of revelation, reason, and sensory experience provides a more comprehensive philosophical basis for developing human beings as spiritual-rational entities, managing nature as a trust (amanah), and positioning God as the center of values and the ultimate orientation of truth. Therefore, Islamic epistemology proves to be more relevant in addressing the challenges of modern education and in formulating an educational paradigm oriented toward the formation of the insān kāmil (holistic human being).